Blast furnace injection mixed pulverized coal
By using iron-based MOF materials and its derivatives as combustion aids in blast furnace spraying mixed coal powder, the porous skeleton of Fe2O3 and activated carbon is formed, and the problems of high ignition temperature and low combustion efficiency of blast furnace spraying coal powder are solved, and the further development is achieved Efficient combustion and lower production costs.
Patent Information
- Application Number
- CN202411454910.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-27
AI Technical Summary
The ignition temperature of existing blast furnaces is relatively high and the combustion efficiency is relatively low, which affects the stable operation of the blast furnace.
Using iron-based MOF materials and/or their derivatives as combustion aids, the combustion is synergistically catalyzed by adding bituminous coal and anthracite to the mixed coal powder in the blast furnace, and forming a porous framework of Fe2O3 and activated carbon before or after spraying, and the combustion is synergistically catalyzed. Reduce the ignition temperature and improve combustion efficiency.
It significantly reduces the ignition temperature of mixed coal powder, improves combustion efficiency, ensures fuel utilization and iron smelting efficiency in the blast furnace, reduces the use of coke, and reduces production costs.
Smart Images

Figure BDA0005090171880000091 
Figure BDA0005090171880000101 
Figure BDA0005090171880000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel smelting, and in particular to a blast furnace spraying mixed coal powder. Background Art
[0002] Pulverized coal injection in blast furnaces is one of the effective means to increase iron, save coke, save energy and reduce consumption in the production process of blast furnaces. If the ash softening temperature of the raw materials injected into blast furnaces is too low or too high, it will have an adverse effect on the stable operation of the blast furnace. In order to achieve the stable operation of the blast furnace, pulverized coal with an ash softening temperature between 1250℃ and 1400℃ is mainly used as the injection raw material. The ash of bituminous coal has a high calcium content and a low ash melting point. The softening temperature is far lower than the blast furnace injection standard and is not suitable for direct application in blast furnace injection. At present, the main mode of mixed injection of bituminous coal and anthracite is adopted. For example, patent document CN110205420A discloses an optimization method for high-calcium bituminous coal for blast furnace injection based on the ash melting characteristics. The mixed injection of high-calcium bituminous coal and anthracite makes the ash softening temperature reach above 1250℃. Patent document CN110592299A discloses a coal blending method for blast furnace injection of high-calcium low-melting-point bituminous coal and its blended coal, wherein high-calcium Shendong bituminous coal and anthracite are mixed and injected at a high ratio to increase the ash softening temperature. In the above method, although the ash softening temperature of the coal powder is increased, the combustion characteristics of the coal powder are difficult to ensure, such as high ignition temperature and low combustion efficiency. Therefore, it is necessary to provide a blast furnace injection mixed coal powder with low ignition temperature and high combustion efficiency. Summary of the invention
[0003] The main purpose of the present invention is to provide a blast furnace injection mixed coal powder to solve the problems of high ignition temperature and low combustion efficiency of the mixed coal powder in the prior art.
[0004] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a mixed coal powder for blast furnace injection is provided. Calculated by weight, the mixed coal powder for blast furnace injection comprises: 30-55 parts of bituminous coal, 40-65 parts of anthracite, and 0.5-3 parts of a combustion aid; wherein the combustion aid comprises an iron-based MOF material and / or an iron-based MOF material derivative.
[0005] Further, the iron-based MOF material derivative is prepared by subjecting the iron-based MOF material to a first carbonization treatment under a first inert atmosphere;
[0006] Preferably, the temperature of the first carbonization treatment is 600-800°C.
[0007] Furthermore, the iron-based MOF material derivative is prepared by loading the metal compound on the iron-based MOF material matrix;
[0008] Preferably, the metal compound comprises a calcium-containing compound and / or a lanthanum-containing compound;
[0009] More preferably, the metal compound comprises calcium chloride and / or lanthanum chloride.
[0010] Furthermore, the preparation of the iron-based MOF material derivative includes: mixing the iron-based MOF material matrix with a solution containing a metal compound, and obtaining a modified iron-based MOF material after impregnation and adsorption;
[0011] After the modified iron-based MOF material is dried, an iron-based MOF material derivative is obtained.
[0012] Furthermore, after the modified iron-based MOF material is dried, the method further includes: subjecting the dried modified iron-based MOF material to a second carbonization treatment under a second inert atmosphere to obtain an iron-based MOF material derivative;
[0013] Preferably, the temperature of the second carbonization treatment is 600-800°C.
[0014] Furthermore, the mass ratio of the iron-based MOF material matrix to the metal compound is 100:(5-30).
[0015] Furthermore, the iron-based MOF material is formed by self-assembly of iron ions and organic ligands, wherein the organic ligands include at least one of 2-hydroxyterephthalic acid and 2,5-dihydroxyterephthalic acid.
[0016] Furthermore, in the mixed pulverized coal injected into the blast furnace, the mass content of volatile matter is 15% to 21%, and the mass content of ash is 5% to 10%;
[0017] Preferably, in the ash of the mixed pulverized coal injected into the blast furnace, the mass content of silicon dioxide is 40% to 48%, and the mass content of calcium oxide is 8% to 18%.
[0018] The D70 particle size of mixed pulverized coal for blast furnace injection is less than 75μm;
[0019] The return flame length of the mixed pulverized coal injected into the blast furnace is less than 80mm, and the ash softening temperature is 1300-1380℃.
[0020] Furthermore, in the bituminous coal, the mass content of volatile matter is 27% to 34%, the mass content of ash is 2% to 10%, and the mass content of sulfur is 0.2% to 0.7%;
[0021] Preferably, in the bituminous coal, the mass content of volatile matter is 27.64% to 33.85%, the mass content of ash is 2.42% to 9.04%, and the mass content of sulfur is 0.256% to 0.699%;
[0022] Preferably, the mass content of calcium oxide in the ash of bituminous coal is 15% to 35%;
[0023] Preferably, the cartridge calorific value of bituminous coal is 24000-29000 kJ / kg, and the ash softening temperature is 1000-1200°C;
[0024] More preferably, the cartridge calorific value of bituminous coal is 24123.47-28848.65 kJ / kg, and the ash softening temperature is 1017-1200°C;
[0025] Preferably, the return flame length of the bituminous coal is 201-800 mm.
[0026] Furthermore, in the anthracite, the mass content of volatile matter is 7% to 11%, the mass content of ash is 9% to 12%, and the mass content of sulfur is 0.4% to 0.7%;
[0027] Preferably, the calorific value of anthracite is 30000-33000 kJ / kg, and the ash softening temperature is 1300-1500°C;
[0028] More preferably, the cartridge calorific value of anthracite is 30051-32269 kJ / kg, and the ash softening temperature is 1300-1450°C.
[0029] By applying the technical solution of the present invention, by introducing iron-based MOF materials and / or iron-based MOF material derivatives as combustion improvers, before or after the mixed coal powder including the combustion improver is sprayed into the blast furnace, the combustion improver can form a porous skeleton including Fe2O3 and activated carbon. On the one hand, Fe2O3 and CaO in the bituminous coal ash synergistically catalyze to promote the combustion of the mixed coal powder. On the other hand, the activated carbon is combustible and can improve the calorific value and comprehensive combustion characteristic index of the mixed coal powder. In addition, the combustion improver will not deteriorate the initial combustion state of the mixed coal powder. Therefore, under the synergistic effect of bituminous coal, anthracite and the combustion improver, the ignition temperature of the mixed coal powder can be significantly reduced and the combustion efficiency can be improved. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0031] As described in the background of the present invention, the existing mixed coal powder has the problems of high ignition temperature and low combustion efficiency. In order to solve the above problems, in a typical embodiment of the present invention, a mixed coal powder for blast furnace injection is provided, which comprises, by weight, 30 to 55 parts of bituminous coal, 40 to 65 parts of anthracite, and 0.5 to 3 parts of a combustion aid; wherein the combustion aid comprises an iron-based MOF material and / or an iron-based MOF material derivative.
[0032] The mixed pulverized coal for blast furnace injection of the present invention can be directly injected into the blast furnace through the injection equipment, and participate in the reduction reaction together with the iron ore to improve the utilization rate of the fuel in the furnace and the ironmaking efficiency. The use of the mixed pulverized coal for blast furnace injection can reduce the use of coke, thereby reducing the production cost. During injection, the temperature of the mixed pulverized coal is usually 200-300°C, and this temperature range can ensure that the mixed pulverized coal can be burned quickly after being injected into the blast furnace. The temperature in the blast furnace is usually 1500-2000°C, and the mixed pulverized coal can be burned when injected into the blast furnace.
[0033] Iron-based MOF material is a material with a highly ordered porous structure, which is formed by self-assembly of iron ions and organic ligands. Iron-based MOF material derivatives refer to new materials obtained by modifying or treating iron-based MOF materials by chemical or physical methods. For example, it can be a product obtained by heat treating an iron-based MOF material, or it can be a product obtained by introducing metal salts, metal nanoparticles or metal oxides into the surface or pores of an iron-based MOF material. The present invention does not make too many restrictions here.
[0034] The combustion aid includes iron-based MOF materials and / or iron-based MOF material derivatives. It can be understood that the combustion aid may include only iron-based MOF materials, only iron-based MOF material derivatives, or both iron-based MOF materials and iron-based MOF material derivatives.
[0035] Before or after the blast furnace-injected mixed coal powder is injected into the blast furnace, the iron ions in the combustion improver can be converted into Fe2O3, and the organic ligand can be converted into activated carbon with a high specific surface area, thereby forming a porous skeleton including Fe2O3 and activated carbon. On the one hand, Fe2O3 and CaO in the bituminous coal ash synergistically catalyze to promote the combustion of the mixed coal powder. On the other hand, the activated carbon is combustible and can improve the calorific value and comprehensive combustion characteristic index of the mixed coal powder. In addition, the combustion improver will not deteriorate the initial combustion state of the mixed coal powder. Therefore, under the synergistic effect of bituminous coal, anthracite and the combustion improver, the ignition temperature of the mixed coal powder can be significantly reduced and the combustion efficiency can be improved.
[0036] When the combustion aid only includes iron-based MOF materials, the blast furnace-injected mixed coal powder including the combustion aid is injected into the blast furnace and then burned. During the combustion process, the iron ions in the combustion aid are converted into Fe2O3, and the organic ligands are converted into activated carbon with a high specific surface area. The porous structure of MOF is retained, thereby forming a porous skeleton including Fe2O3 and activated carbon. This porous structure helps to increase the specific surface area of the material, thereby improving the catalytic activity.
[0037] The iron-based MOF material derivative can be obtained by heat-treating the iron-based MOF material. In some embodiments, the iron-based MOF material derivative is obtained by subjecting the iron-based MOF material to a first carbonization treatment under a first inert atmosphere. In the first carbonization treatment, the organic ligands in the iron-based MOF material decompose to form activated carbon with a high specific surface area, and the iron ions in the iron-based MOF material are converted into Fe2O3. The iron-based MOF material derivative includes a porous skeleton of Fe2O3 and activated carbon, which has the advantages of large specific surface area and strong catalytic activity. It is directly used as a combustion aid and is sprayed into a blast furnace together with bituminous coal and anthracite for combustion. In this way, before combustion, the above-mentioned porous skeleton structure is formed in advance, which helps to increase the specific surface area and catalytic activity of the combustion aid, and then sprayed for use, which can further reduce the ignition temperature and improve the combustion efficiency.
[0038] In some preferred embodiments, the temperature of the first carbonization treatment is 600-800° C., for example, 600° C., 650° C., 700° C., 750° C., 800° C. or a range consisting of any two thereof.
[0039] The iron-based MOF material derivative can be formed by introducing a metal compound into the iron-based MOF material. In some embodiments, the iron-based MOF material derivative is prepared by loading the metal compound on the iron-based MOF material matrix. At this time, the iron-based MOF material derivative includes the iron-based MOF material matrix and the metal compound loaded on the iron-based MOF material matrix. The mixed pulverized coal including the iron-based MOF material derivative is sprayed into the blast furnace for combustion. During the combustion process, the iron-based MOF material matrix can be converted into a porous skeleton including Fe2O3 and activated carbon, and the metal compound can be converted into a metal oxide. In this way, under the synergistic catalytic action of Fe2O3, metal oxides and CaO in bituminous coal and anthracite, the combustion of the mixed pulverized coal can be further promoted, the ignition temperature can be reduced and the combustion efficiency can be improved.
[0040] In some embodiments, the metal compound includes a calcium compound and / or a lanthanum compound. Thus, during the combustion process, the calcium compound and / or the lanthanum compound can be converted into calcium oxide and / or lanthanum oxide, which can be catalyzed together with Fe2O3 and CaO in anthracite to promote the combustion of the mixed coal powder, further reduce the ignition temperature and improve the combustion efficiency. In some preferred embodiments, the metal compound includes calcium chloride and / or lanthanum chloride.
[0041] In some embodiments, the preparation of the iron-based MOF material derivative includes: mixing the iron-based MOF material matrix with a solution containing a metal compound, and obtaining a modified iron-based MOF material after impregnation and adsorption; and drying the modified iron-based MOF material to obtain an iron-based MOF material derivative. In this way, the metal compound is loaded on the iron-based MOF material matrix by impregnation and adsorption, and then excess water is removed by drying to obtain an iron-based MOF material derivative. At this time, the iron-based MOF material derivative includes the iron-based MOF material matrix and the metal compound loaded on the iron-based MOF material matrix.
[0042] In the above embodiment, after the modified iron-based MOF material is dried, the method further includes: subjecting the dried modified iron-based MOF material to a second carbonization treatment under a second inert atmosphere to obtain an iron-based MOF material derivative. During the second carbonization treatment, the iron-based MOF material matrix is converted into a porous skeleton including Fe2O3 and activated carbon, and at the same time, the metal compound is converted into a metal oxide. The iron-based MOF material derivative includes a porous skeleton of Fe2O3 and activated carbon and a metal oxide supported on the porous skeleton. The derivative is directly used as a combustion aid and is sprayed into a blast furnace together with bituminous coal and anthracite for combustion. In this way, before combustion, the above-mentioned porous skeleton structure and metal oxide are pre-formed, which helps to increase the specific surface area and catalytic activity of the combustion aid, and then sprayed for use, which can further reduce the ignition temperature and improve the combustion efficiency.
[0043] In some preferred embodiments, the temperature of the second carbonization treatment is 600-800° C., for example, 600° C., 650° C., 700° C., 750° C., 800° C. or a range consisting of any two thereof.
[0044] The mass ratio of the iron-based MOF material matrix to the metal compound is 100:(5-30), for example, 100:5, 100:10, 100:20, 100:30 or a range consisting of any two of them.
[0045] The present invention does not limit the specific type of iron-based MOF material, and it can be a conventional iron-based MOF material in the art. For example, the iron-based MOF material is formed by self-assembly of iron ions and organic ligands, wherein the organic ligands include at least one of 2-hydroxyterephthalic acid and 2,5-dihydroxyterephthalic acid. The preparation of the iron-based MOF material includes: mixing an iron source (such as an iron salt) with an organic ligand in a solvent, and synthesizing by a solvothermal or hydrothermal method.
[0046] Volatile matter and ash content in the mixed pulverized coal injected into the blast furnace are two important quality indicators, which have an important impact on the operation of the blast furnace and the ironmaking process. In some embodiments, the mass content of volatile matter in the mixed pulverized coal injected into the blast furnace is 15% to 21%, and the mass content of ash is 5% to 10%. By reasonably controlling the content of volatile matter and ash, efficient and stable operation of the blast furnace can be achieved.
[0047] Specifically, volatile matter refers to the sum of gases and liquids that can escape from coal powder when it is heated under air-tight conditions. These gases and liquids mainly include water, methane, carbon dioxide, hydrogen, nitrogen, etc. The level of volatile matter content can reflect the combustion characteristics and calorific value of coal powder. Generally speaking, the higher the volatile matter, the faster the combustion speed of coal powder, which can improve the combustion efficiency of the blast furnace, but the calorific value is relatively low, and the temperature fluctuation in the blast furnace is large, which affects the stability of the furnace condition; the lower the volatile matter, the slower the combustion speed of coal powder, but the calorific value is relatively high, and the combustion process is relatively stable, which is conducive to the stable operation of the blast furnace. The mass content of volatile matter in the mixed coal powder injected into the blast furnace of the present invention is 15% to 21%, which means that the mixed coal powder injected into the blast furnace can take into account the combustion speed and calorific value of the mixed coal powder injected into the blast furnace, and ensure stable combustion.
[0048] Ash refers to the remaining incombustible substances after coal powder is heated to a certain temperature under air-tight conditions. These substances mainly include minerals, oxides, silicates, etc. The ash content can reflect the purity of coal and the amount of residue after combustion. Generally speaking, the lower the ash content, the less residue is produced in the blast furnace and the higher the ironmaking efficiency, but at the same time, the CaO in it is also reduced accordingly, which is not conducive to reducing the ignition temperature and improving the combustion efficiency; the higher the ash content, the more CaO in it is also increased accordingly, which is conducive to reducing the ignition temperature and improving the combustion efficiency, but at the same time, the lower the purity of the coal powder, the more residue is left after combustion. The mass content of ash in the mixed coal powder injected into the blast furnace of the present invention is 5% to 10%. In some preferred embodiments, in the ash of the mixed coal powder injected into the blast furnace, the mass content of silicon dioxide is 40% to 48%, and the mass content of calcium oxide is 8% to 18%, indicating that the mixed coal powder injected into the blast furnace of the present invention can reduce the amount of residue after combustion while reducing the ignition temperature and improving the combustion efficiency.
[0049] The particle size distribution of pulverized coal injected into a blast furnace has an important impact on the operating efficiency and economy of the blast furnace. In some embodiments, the D70 particle size of the mixed pulverized coal injected into the blast furnace is less than 75 μm. The D70 particle size means that 70% of the particle diameters of the mixed pulverized coal injected into the blast furnace are less than or equal to this value. By limiting the D70 particle size of the mixed pulverized coal injected into the blast furnace to less than 75 μm, the combustion efficiency and fluidity of the mixed pulverized coal in the blast furnace are ensured, the combustion efficiency of the pulverized coal in the blast furnace is ensured, and at the same time, the clogging of the injection equipment by excessively large particles is avoided.
[0050] The return flame length and ash softening temperature of the mixed pulverized coal injected into the blast furnace are two important parameters in the ironmaking process, which have an important impact on the operation and efficiency of the blast furnace. In some embodiments, the return flame length of the mixed pulverized coal injected into the blast furnace is less than 80 mm, and the ash softening temperature is 1300-1380°C. By limiting the return flame length and ash softening temperature of the mixed pulverized coal injected into the blast furnace within the above range, the efficient operation of the blast furnace can be ensured.
[0051] Specifically, the return flame length refers to the distance that the flame generated by the combustion of pulverized coal rises in the blast furnace after pulverized coal is injected into the blast furnace. This length can reflect the combustion efficiency of pulverized coal and the temperature distribution in the furnace. If the return flame length is too long, it may cause uneven temperature distribution in the furnace, affecting the reduction and melting of the charge. The return flame length of the mixed pulverized coal injected into the blast furnace of the present invention is less than 80 mm, preferably less than 35 mm, indicating that the blast furnace of the present invention has high combustion efficiency and uniform temperature distribution in the furnace.
[0052] The ash softening temperature refers to the temperature at which the ash (i.e., the inorganic matter in the coal powder) produced after the combustion of the coal powder begins to soften. The ash softening temperature is an important indicator for measuring the quality of coal powder. It affects the combustion of coal powder in the furnace and the fluidity of the slag. If the ash softening temperature is too high, it may cause poor fluidity of the slag, affecting the melting of the charge and the discharge of the slag; if the ash softening temperature is too low, it may cause the slag to soften prematurely, affecting the reduction of the charge. The ash softening temperature of the mixed coal powder injected into the blast furnace of the present invention is 1300-1380°C, indicating that the mixed coal powder injected into the blast furnace of the present invention can be fully burned in the furnace, and the slag has good fluidity, which is beneficial to the melting of the charge and the discharge of the slag.
[0053] The present invention does not limit the specific types of bituminous coal and anthracite, which can be conventional bituminous coal and anthracite in the art. It should be noted that bituminous coal and anthracite are both types of coal, and bituminous coal usually contains a higher volatile matter and produces more smoke when burned. Anthracite has a lower volatile matter content and produces less smoke when burned. Bituminous coal is preferably Shendong bituminous coal, which has the characteristics of low sulfur, low phosphorus, low ash, high calorific value, etc.
[0054] By reasonably controlling the content of volatile matter and ash in bituminous coal and anthracite, the volatile matter and ash in the mixed pulverized coal injected into the blast furnace can meet the above requirements, which is beneficial to improving the energy utilization rate of the mixed pulverized coal injected into the blast furnace and reducing energy waste. For example, in some embodiments, the mass content of volatile matter in bituminous coal is 27% to 34%, the mass content of ash is 2% to 10%, and the mass content of sulfur is 0.2% to 0.7%. In some embodiments, the mass content of volatile matter in anthracite is 7% to 11%, the mass content of ash is 9% to 12%, and the mass content of sulfur is 0.4% to 0.7%.
[0055] In some preferred embodiments, the mass content of volatile matter in the bituminous coal is 27.64% to 33.85%, the mass content of ash is 2.42% to 9.04%, and the mass content of sulfur is 0.256% to 0.699%. In some preferred embodiments, the mass content of calcium oxide in the ash of the bituminous coal is 15% to 35%.
[0056] By reasonably controlling the ash softening temperature of bituminous coal and anthracite, the ash softening temperature of the mixed pulverized coal injected into the blast furnace can meet the above requirements and achieve stable operation of the blast furnace. In some embodiments, the ash softening temperature of bituminous coal is 1000-1200°C, preferably 1017-1200°C, such as 1017°C, 1100°C, 1150°C, 1200°C or any two thereof. In some embodiments, the ash softening temperature of anthracite is 1300-1500°C, preferably 1300-1450°C, such as 1300°C, 1350°C, 1400°C, 1450°C or any two thereof.
[0057] In order to further improve the combustion efficiency and reduce pollutants generated by incomplete combustion, in some embodiments, the return flame length of the bituminous coal is 201-800 mm. The appropriate return flame length helps to fully mix the mixed coal powder with the air, maintain uniform heat distribution in the blast furnace, and thus improve the overall thermal efficiency.
[0058] The calorific value of the cartridge refers to the heat released during combustion, and the calorific value of the cartridge can be measured using a cartridge calorimeter. The calorific value of the cartridge is an important indicator for measuring coal quality. In some embodiments, the calorific value of the cartridge of bituminous coal is 24000-29000 kJ / kg, preferably 24123.47-28848.65 kJ / kg. In some embodiments, the calorific value of the cartridge of anthracite is 30000-33000 kJ / kg, preferably 30051-32269 kJ / kg. By controlling the calorific value of the cartridge of bituminous coal and anthracite within the above range, energy efficiency and energy utilization efficiency can be improved.
[0059] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0060] Example 1
[0061] The mixed pulverized coal for blast furnace injection in this embodiment includes 50% bituminous coal, 48% anthracite, and 2% combustion aid in terms of mass percentage; wherein the properties and ash composition of the bituminous coal and anthracite are shown in Tables 1 and 2. The combustion aid is an iron-based MOF material, which is self-assembled by iron ions and organic ligands, and the organic ligand is 2-hydroxyterephthalic acid;
[0062] The preparation of the iron-based MOF material includes: weighing 5.4 g of ferric chloride hexahydrate (FeCl3·6H2O), dissolving it in 100 mL of deionized water, stirring until completely dissolved to form a uniform iron ion solution; weighing 3.0 g of 2-hydroxyterephthalic acid (C8H6O6), dissolving it in 100 mL of a mixed solvent of ethanol and deionized water (volume ratio 1:1), heating and stirring in a 60°C water bath until completely dissolved; slowly adding the iron ion solution to the organic ligand solution, keeping stirring to avoid precipitation caused by excessive local concentration, continuing stirring for 1 hour to ensure uniform mixing of the solution, and adjusting the pH of the solution with hydrochloric acid or sodium hydroxide. H to 4-6, the adjusted solution is placed in an ultrasonic instrument and ultrasonically treated for 30 minutes to promote the self-assembly of iron ions and organic ligands; the treated mixed solution is transferred to a 100mL high-pressure reactor, sealed and subjected to hydrothermal reaction at 120-150°C for 12-24 hours, and naturally cooled to room temperature; the product in the reactor is taken out, washed with deionized water 3 times to remove unreacted precursors and impurities, and then washed with ethanol 2 times; the precipitate is collected with a vacuum filtration device to obtain an iron-based MOF product; the filtered product is placed in a drying oven at 60°C and dried for 12 hours until the product is completely dry to obtain an iron-based MOF material;
[0063] The mixed pulverized coal for blast furnace injection of this embodiment is used for blast furnace injection.
[0064] Embodiment 2-3
[0065] Compared with Example 1, the difference is that the contents of bituminous coal, anthracite and combustion aid in the mixed pulverized coal injected into the blast furnace are different, as shown in Table 3.
[0066] Example 4
[0067] Compared with Example 1, the difference is that the combustion aid is a modified MOF material, the modified MOF material includes an iron-based MOF material and calcium chloride loaded on the iron-based MOF material, and the mass ratio of the iron-based MOF material to the calcium chloride is 100:10;
[0068] Among them, the preparation of modified iron-based MOF materials includes: calculating by mass ratio, according to the mass ratio of iron-based MOF material to CaCl2 of 100:10, weighing an appropriate amount of anhydrous calcium chloride, dissolving the calcium chloride in ethanol or deionized water to form a uniform calcium chloride solution; adding the iron-based MOF material to the calcium chloride solution, and keeping stirring for 4 hours to ensure that the calcium chloride is evenly distributed on the surface and pores of the MOF; during the stirring process, using ultrasonic assisted treatment for 30 minutes to further promote the penetration of calcium chloride in the MOF; the impregnated solution is vacuum filtered to collect the solid phase; the obtained solid phase is placed in a vacuum drying oven at 60°C and dried for 12 hours to ensure that the solvent is completely evaporated and the calcium chloride is firmly attached to the MOF material to obtain a modified MOF material.
[0069] Example 5
[0070] Compared with Example 1, the difference is that the combustion aid is a modified MOF material, the modified MOF material includes an iron-based MOF material and lanthanum chloride loaded on the iron-based MOF material, and the mass ratio of the iron-based MOF material to calcium chloride is 100:10;
[0071] The preparation of the modified MOF material includes: weighing an appropriate amount of anhydrous lanthanum chloride according to the mass ratio of iron-based MOF material to calcium chloride of 100:10, dissolving it in ethanol or deionized water to form a uniform lanthanum chloride solution; slowly adding the iron-based MOF material to the lanthanum chloride solution, stirring continuously for 4 hours to ensure that the lanthanum chloride is evenly distributed on the surface and pores of the MOF material, and ultrasonically treating for 30 minutes to promote the deep penetration of lanthanum chloride in the MOF material; collecting the impregnated MOF by vacuum filtration, and then placing the obtained MOF in a vacuum drying oven at 60°C for 12 hours to ensure that the solvent is completely evaporated and the lanthanum chloride is stably loaded on the MOF material to obtain a modified MOF material.
[0072] Example 6
[0073] Compared with Example 1, the difference is that the iron-based MOF material in Example 1 is calcined at 700°C in nitrogen for 2 hours to obtain an iron metal organic framework-derived porous carbon composite material, and the iron metal organic framework-derived porous carbon composite material is used as a combustion aid.
[0074] Example 7
[0075] Compared with Example 5, the difference is that the modified MOF material in Example 5 is calcined at 700°C in nitrogen for 2 hours to obtain an iron-metal organic framework-derived porous carbon composite material, and the iron-metal organic framework-derived porous carbon composite material is used as a combustion aid.
[0076] Example 8
[0077] Compared with Example 4, the difference is that the loading amount of calcium chloride is different, and the mass ratio of the iron-based MOF material to calcium chloride is 100:30.
[0078] Example 9
[0079] Compared with Example 5, the difference is that the loading amount of lanthanum chloride is different, and the mass ratio of iron-based MOF material to lanthanum chloride is 100:30.
[0080] Comparative Example 1
[0081] Compared with Example 1, the difference is that no combustion aid is contained.
[0082] Comparative Example 2
[0083] Compared with Example 1, the difference is that the mixed pulverized coal injected into the blast furnace of this comparative example includes 50% bituminous coal, 45% anthracite and 5% combustion aid in terms of mass percentage.
[0084] Comparative Example 3
[0085] Compared with Example 1, the difference is that the mixed pulverized coal injected into the blast furnace of this comparative example includes 50% bituminous coal, 49.8% anthracite and 0.2% combustion aid in terms of mass percentage.
[0086] Test example
[0087] The mixed pulverized coal for blast furnace injection of the embodiment and the comparative example is used for blast furnace injection, and the specific operation is as follows: the bituminous coal and anthracite with a particle size less than 200 mesh that have been sieved are mixed with the combustion aid, and the mixing ratio is according to the test plan. The prepared sample is put into an oven at a temperature of 105°C and a drying time of 4 hours to fully remove the adsorbed water in the sample, and then the sample is taken and weighed, and its injection effect is evaluated according to the following test method.
[0088] 1. Test of ash softening temperature
[0089] Tested using GB / T 219 coal ash fusibility test method
[0090] 2. Test of return flame length
[0091] A long tube test device is used to measure the length of the return flame when the coal powder explodes to determine whether the coal powder is explosive and the strength of its explosiveness. Use 1g of coal powder sample with a particle size of less than 0.2mm, spray it into a 1050℃ fire source in a glass tube, and judge its explosiveness by the length of its return flame.
[0092] 3. Test of ignition temperature
[0093] The ignition point refers to the temperature at which coal begins to burn when it is heated to the point where an oxidant (air) and coal coexist. The solid oxidant method is used for testing. Air-dried coal samples with a particle size of less than 0.2 mm are used. After drying, they are mixed with sodium nitrite at a mass ratio of 1:0.75. The coal powder samples are placed on a platinum sheet in a micro-electric furnace and heated at a heating rate of 4.5-5°C / min. The pressure generated by the coal explosion causes the water column under the ignition point determination device to show a significant change in temperature or volume at the moment of descent. The instantaneous temperature of the coal sample when it explodes is the ignition point of the coal powder.
[0094] 4. Combustion rate test
[0095] Using the WCT-2C microcomputer differential thermal balance produced by Beijing Optical Instrument Factory, when doing TG experiments, first weigh the weight of the coal powder sample m0, then add the coal powder into the sample crucible, and place the crucible on the differential thermal balance, and heat the coal powder at a certain heating rate (20℃ / min). As the temperature rises, the combustion process can be briefly described as follows: the coal powder is first heated rapidly, followed by degassing and rapid thermal decomposition, then the volatile matter is burned, and finally the residual carbon (or semi-coke) and oxygen are burned in a multiphase reaction until the coal powder is completely burned. The mass of the combustion product is m1, and the combustion rate is calculated according to the combustion rate = (m0-m1) / m0.
[0096] The test results are shown in Table 4.
[0097] Table 1 Properties of bituminous coal and anthracite in Example 1
[0098]
[0099] Table 2 Ash composition of bituminous coal and anthracite in Example 1 (in wt%)
[0100] Coal Type <![CDATA[SiO2]]> <![CDATA[Al2O3]]> CaO <![CDATA[Fe2O3]]> <![CDATA[SO3]]> <![CDATA[K2O]]> <![CDATA[TiO2]]> MgO MnO other bituminous coal 22.44 17.86 33.62 8.01 16.63 0.26 0.68 / 0.27 0.20 anthracite 47.68 36.44 3.93 4.36 3.18 0.76 1.82 0.60 0.38 0.82
[0101] Table 3 Composition of mixed pulverized coal for blast furnace injection
[0102] serial number Bituminous coal (wt%) Anthracite (wt%) Combustion aid (wt%) Example 1 50 48 2 Example 2 35 62 3 Example 3 55 44 1 Comparative Example 2 50 45 5 Comparative Example 3 50 49.8 0.2
[0103] Table 4 Spraying effect
[0104]
[0105]
[0106] According to Table 4, the ash softening temperature of the mixed pulverized coal in Examples 1 to 7 is 1348 to 1371°C, the return flame length is 0 to 34 mm, which meets the requirements of blast furnace injection, the ignition temperature is 322 to 368°C, and the combustion rate of the mixed pulverized coal injected in the blast furnace is 78 to 85%. The mixed pulverized coal in Examples 1 to 7 is easy to burn in the blast furnace and has a high combustion utilization rate, so the heat supply is more sufficient, the comprehensive combustion characteristics are better, and the cost is significantly saved.
[0107] Comparing Example 2 with Example 3, it can be seen that when the bituminous coal content increases, the ignition temperature decreases, and the combustion rate in the blast furnace decreases slightly, but still maintains a high level. It can be seen that the present invention can achieve high-ratio high-calcium bituminous coal for blast furnace injection by adding a combustion aid.
[0108] Comparative Examples 4 to 7 show that when calcium chloride or lanthanum chloride is loaded on the surface of the iron-based MOF material, the ignition temperature is further reduced and the combustion rate is further improved. It can be seen that during the injection combustion, calcium chloride or lanthanum chloride can be converted into calcium oxide or lanthanum oxide at high temperature, and together with Fe2O3 and activated carbon, promote the combustion of the mixed coal powder. The metal organic framework is calcined in nitrogen to obtain an iron metal organic framework-derived porous carbon composite material, which is then sprayed for use. The pre-formed Fe2O3 and porous carbon composite framework make its specific surface area and catalytic activity higher than that of the uncalcined one, and the injection combustion characteristics are better.
[0109] In summary, the present invention adds a metal organic framework with iron as the metal central ion as a combustion aid to a blend of high-calcium bituminous coal and anthracite. During the combustion process, the iron-based MOF material is gradually converted into a porous skeleton composed of Fe2O3 and activated carbon under high temperature. Fe2O3 and CaO in the bituminous coal ash catalyze and promote the combustion of the mixed coal powder. The activated carbon nanoparticles are combustible, thereby significantly reducing the ignition point of the mixed coal powder, improving the combustion efficiency and the comprehensive combustion characteristic index, and can simultaneously increase the amount of bituminous coal used, and the practical application value and economic benefits are significant.
[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A blast furnace injection mixed coal powder, characterized in that: Calculated by weight, the mixed pulverized coal for blast furnace injection includes: 30-55 parts of bituminous coal, 40-65 parts of anthracite, and 0.5-3 parts of a combustion aid; wherein the combustion aid includes an iron-based MOF material and / or an iron-based MOF material derivative.
2. The mixed pulverized coal injection method for blast furnace according to claim 1, characterized in that: The iron-based MOF material derivative is prepared by subjecting the iron-based MOF material to a first carbonization treatment under a first inert atmosphere; Preferably, the temperature of the first carbonization treatment is 600-800°C.
3. The mixed pulverized coal injection method for blast furnace according to claim 1, characterized in that: The iron-based MOF material derivative is prepared by loading a metal compound on an iron-based MOF material matrix; Preferably, the metal compound comprises a calcium-containing compound and / or a lanthanum-containing compound; More preferably, the metal compound comprises calcium chloride and / or lanthanum chloride.
4. The mixed pulverized coal injection method for blast furnace according to claim 3, characterized in that: The preparation of the iron-based MOF material derivative comprises: mixing the iron-based MOF material matrix with a solution containing a metal compound, and obtaining a modified iron-based MOF material after impregnation and adsorption; After the modified iron-based MOF material is dried, the iron-based MOF material derivative is obtained.
5. The mixed pulverized coal injection method for blast furnace according to claim 4, characterized in that: After drying the modified iron-based MOF material, the method further includes: subjecting the dried modified iron-based MOF material to a second carbonization treatment under a second inert atmosphere to obtain the iron-based MOF material derivative; Preferably, the temperature of the second carbonization treatment is 600-800°C.
6. The mixed pulverized coal injection method for blast furnace according to claim 4, characterized in that: The mass ratio of the iron-based MOF material matrix to the metal compound is 100:(5-30).
7. The blast furnace mixed pulverized coal injection method according to any one of claims 1 to 6, characterized in that: The iron-based MOF material is formed by self-assembly of iron ions and organic ligands, wherein the organic ligands include at least one of 2-hydroxyterephthalic acid and 2,5-dihydroxyterephthalic acid.
8. The blast furnace mixed pulverized coal injection method according to any one of claims 1 to 6, characterized in that: The mass content of volatile matter in the mixed pulverized coal injected into the blast furnace is 15% to 21%, and the mass content of ash is 5% to 10%; Preferably, in the ash of the mixed pulverized coal injected into the blast furnace, the mass content of silicon dioxide is 40% to 48%, and the mass content of calcium oxide is 8% to 18%; Preferably, the D70 particle size of the mixed pulverized coal injected into the blast furnace is less than 75 μm; Preferably, the return flame length of the mixed pulverized coal injected into the blast furnace is less than 80 mm, and the ash softening temperature is 1300-1380°C.
9. The blast furnace mixed pulverized coal injection method according to any one of claims 1 to 6, characterized in that: The bituminous coal has a volatile matter content of 27% to 34% by mass, an ash content of 2% to 10% by mass, and a sulfur content of 0.2% to 0.7% by mass; Preferably, in the bituminous coal, the mass content of volatile matter is 27.64% to 33.85%, the mass content of ash is 2.42% to 9.04%, and the mass content of sulfur is 0.256% to 0.699%; Preferably, the mass content of calcium oxide in the ash of the bituminous coal is 15% to 35%; Preferably, the cartridge calorific value of the bituminous coal is 24000-29000 kJ / kg, and the ash softening temperature is 1000-1200°C; More preferably, the cartridge calorific value of the bituminous coal is 24123.47-28848.65 kJ / kg, and the ash softening temperature is 1017-1200°C; Preferably, the return flame length of the bituminous coal is 201-800 mm.
10. The blast furnace mixed pulverized coal injection method according to any one of claims 1 to 6, characterized in that: The anthracite has a volatile matter content of 7% to 11%, an ash content of 9% to 12%, and a sulfur content of 0.4% to 0.7%. Preferably, the anthracite has a cartridge calorific value of 30,000 to 33,000 kJ / kg and an ash softening temperature of 1,300 to 1,500°C; More preferably, the anthracite has a barrel calorific value of 30051-32269 kJ / kg and an ash softening temperature of 1300-1450°C.
Citation Information
Cited By
Method for improving combustion rate of blast furnace injection pulverized coal by using hydrogen-rich gas
CN120425094A